Technetium 99m–Labeled VQ Peptide: A New Imaging Agent for the Early Detection of Tumors or Premalignancies - Jiyun Shi; Liyang Cui; Bing Jia; Zhaofei Liu; Peng He; Chengyan Dong; Xiaona Jin; Huiyun Zhao; Fang Li; Fan Wang (Molecular Imaging)
There is a critical need to develop diagnostic procedures enabling early detection of tumors while at a curable stage. Technetium 99m ( 99m Tc)-labeled VQ peptide ( 99m Tc-HYNIC-VQ) identified through screening phage display peptide libraries against fresh human colonic adenomas was prepared and evaluated for tumor detection. 99m Tc-HYNIC-VQ was prepared by a non-SnCl 2 method with more than 99% radiochemical purity. The biodistribution in the HT-29 tumor model showed that although the absolute tumor uptake values were relatively low (0.60 ± 0.09, 0.41 ± 0.09, 0.36 ± 0.18, and 0.19 ± 0.08 %ID/g at 0.5, 1, 2, and 4 hours postinjection, respectively), the tumor uptake was higher than that of any of the other organs except for the kidneys at any time point examined, which led to the high tumor to nontarget ratios. The tumors and inflammation were clearly visualized with high contrast. Although the mechanism of accumulation of radiolabeled VQ peptide in tumors and inflammation needs to be further investigated, 99m Tc-HYNIC-VQ is a promising imaging agent for the early detection of tumors or premalignancies, at least for screening patients with a high risk of developing cancers.